Experiences of Elementary School Counselors and Students in Using Reality Art Therapy to Address Chronic Conditions. (January 2019) - Davis, Eric; Smith-Adcock, Sondra; Towns, Lindsey
Elementary school counselors are frequently called on to provide counseling services for children with chronic conditions. However, counselors' training and professional development in this area is lacking. Myriad behavioral, social, and academic issues can result from a child's chronic condition. This qualitative study examined elementary school counselors' and students' perceptions of an integrated reality therapy and art therapy intervention and revealed four themes. We discuss implications for elementary school counselors.